2018
DOI: 10.5152/turkjsurg.2018.3889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the non-mortal gunshot and handmade explosive blast traumas during a low-intensity conflict on urban terrain

Abstract: Contrary to the expected, gunshot casualties were found to be more likely to suffer from extremity injuries than blast casualties did, and it should be noted that blast trauma casualties tend to have multiple compartment injuries that should not be missed. Ocular ruptures are also common, especially with blast injuries, warranting equipping the personnel with protective goggles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Accordingly, in another study, the injury rate that occurred due to blast trauma was 58.3%. [9] However, in the present study, the pistol-rifle/explosive ratio was found to be 38.7%, as opposed to the previous ones. This may be due to the inclusion of only those cases who could reach the Role II hospital alive.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Accordingly, in another study, the injury rate that occurred due to blast trauma was 58.3%. [9] However, in the present study, the pistol-rifle/explosive ratio was found to be 38.7%, as opposed to the previous ones. This may be due to the inclusion of only those cases who could reach the Role II hospital alive.…”
Section: Discussioncontrasting
confidence: 95%
“…Differences have been observed in injury sites with the change of weapon technology and combat style. In the study conducted by Güven et al, [9] extremities were the most frequently affected site in bullet injuries, while head and neck injuries were observed in blast injuries along with extremities. In our study, the thorax region was most commonly affected in bullet injuries, while the head and neck region was affected in blast injuries.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Guven et al found that extremities were the most frequently affected body region in gunshot wounds[26]. In the previous studies, Akoglu et al, found the extremities and Durdu et al, found the upper extremities as most affected body region in gunshot wounds…”
mentioning
confidence: 96%